(untitled) (Research, Society and Development, 2022)
Fiber post retention is associated with the degree of adaptation to the root wall with different luting agents. However, there is no unanimity regarding the superiority of one cement over the other. the purpose of this study was to evaluate the bond strength of fiberglass posts cemented to bovine dentin with different luting agents. Thirty bovine teeth were selected, and their crowns removed below the cementoenamel junction. the dental pulps were removed, then the canals were prepared with a working length of 11 mm. The roots of bovine teeth were divided into three groups according to the material used for cementation: group i (n=10) - glass ionomer (fuji), group ii (n=10) - dual relyx resin cement (3m special), and group iii (n=10) - multilink chemically activated resin cement (ivoclar/vivadent). Before cementation, all posts were cleaned with 37% phosphoric acid for the 30s and the posts of groups ii and iii were silanized. The dental roots were transversally sectioned in three thirds after cementation: cervical, middle, and apical and each segment obtained was submitted to the push-out test. the highest values ​​of bond strength were presented by relyx resin cement, followed by fuji glass ionomer cement and multilink chemically activated resin cement, respectively. Higher bond strength values ​​were verified in the cervical third regardless of the group evaluated (p<0.05). It was concluded that there was a significant difference between the degree of adhesion presented by the different cementing agents used and between the different root segments.